Pengaruh Ethical Leadership Terhadap Affective Commitment Dan Job Satisfaction yang Dimediasi Oleh Psychological Empowerment - Inesia, Dwi; Ardiyanti, Niken (UI Scholars Hub, 2021)
This study discusses the effect of Ethical Leadership on Affective commitment and Job Satisfaction which’s mediated by Psychological Empowerment. Respondents of this study were 217 State Civil Servants in the DKI Jakarta area Hypothesis testing using Lisrel’s Structural Equation Model (SEM) 8.5 method. Hypothesis test result show that Ethical Leadership has a direct positive effect, both on Affective Commitment (SLF 0,25 and T-Value 2,53), and on Job Stisfaction (SLF 0,26 and T-Value 2,61). Psychologcal Empowerment partially mediateds the effect between Ethical Leadership and Af- fective Commitment (total effect value 0,8393). Psychologcal Empowerment also partially mediateds the effect between Ethical Leadership and Job Satisfaction (total effect value 0,8742). This shows that Psychological Empowerment in Affective Commitment and Job Satisfaction is vital enough to increase the positive impact on Affective Commitment and Job Satisfaction State Civil Servants in the DKI Jakarta area. Although Ethical Leadership also has direct effect, however, when using indirect effect the result will be stronger.